Environmental Costs of Fossil Fuels : A Rapid Assessment Method with Application to Six Cities - Lvovsky, Kseniya; Hughes, Gordon; Maddison, David; Ostro, Bart; Pearce, David (World Bank, Washington, DC, 2014)
Among the key external effects of fossil fuel contribution are urban air pollution, and changes in global climate. A study of six cities in developing countries, and transition economies estimates the magnitude of these effects, and, examines how various fuels, and pollution sources contribute to health damages, and other environmental costs. The study develops a simple, but robust method for rapid assessment of these damages. By linking the damage to a particular fuel use, or pollution source, the method makes possible cost-benefit analysis of pollution abatement measures. The findings show very high levels of environmental damage, and reveal large sectoral differences. By far the greatest share of the total damage, is that to human health, from exposure to ambient particulates, caused mainly by small pollution sources, such as vehicles, and household stoves. Large industries, and power plants account for a smaller proportion of health damage, but are the major contributors to carbon dioxide emissions, which have an impact on global climate. The complex relationships between pollution sources, and environmental effects, highlight the need for a skillful mix of policy instruments, built on rigorous analysis. The damage assessment method proposed herein, provides a useful analytical tool, to be easily applied to other urban areas.